Three-dimensional continuous diamond / metal composite material and preparation method and application thereof
By constructing a three-dimensional continuous diamond/metal composite material and using a silicon carbide protective layer to connect diamond particles, the problems of traditional composite materials in interface optimization and forming processes are solved, and the characteristics of high thermal conductivity, low expansion and low cost are achieved. It is suitable for multiple A kind of application scenario.
Patent Information
- Application Number
- CN202411760833.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Traditional diamond/metal composites have problems such as high cost, low efficiency, unstable and difficult to prepare complex structures in interface optimization and forming processes, and cannot meet the needs of high thermal conductivity, low expansion and low cost.
By constructing a three-dimensional continuous diamond/metal composite material, using a silicon carbide protective layer to connect diamond particles to form a network, and preparing it through the slurry preparation, granulation, molding, pyrolysis and sintering process, the mutual permeation between diamond and metal network is achieved to form a high level Heat-conducting, low-expansion composite material.
The diamond volume fraction, thermal conductivity and thermal expansion coefficient are highly adjustable, and have the characteristics of high thermal conductivity, low expansion and excellent strength. At the same time, the process is short and the cost is low, and it is suitable for heat dissipation, wear resistance and bulletproof materials.
Smart Images

Figure CN119220848A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a three-dimensional continuous diamond / metal composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the electronics industry, military field, aerospace and other fields, the demand for high power density and high reliability power electronic devices is increasing, which puts higher requirements on high thermal conductivity and low expansion heat dissipation materials. Traditional metal heat dissipation materials can no longer meet the heat dissipation needs of these high-power devices. Metal-based composite materials have gradually replaced traditional heat dissipation materials because they combine the mechanical properties of metals and the high thermal conductivity of reinforcements. Common metal-based composite heat dissipation materials include aluminum silicon, silicon carbide / aluminum, diamond / aluminum and diamond / copper.
[0003] Diamond / metal composites, also known as diamond particle reinforced metal matrix composites, are a type of particle-reinforced metal matrix composites formed by uniformly dispersing diamond particles in metal. This composite material combines the advantages of metal and diamond materials. Diamond is one of the materials in nature with excellent thermal conductivity and low thermal expansion coefficient, while copper, aluminum, magnesium, etc. also have excellent thermal conductivity.
[0004] However, due to the special crystal structure of diamond, the interface optimization mechanism and process between it and the metal matrix are very complicated, which limits the transmission and transfer of the excellent properties of diamond to composite materials. The key to promoting the research and development and application of diamond / metal composite materials is to achieve the best optimization of the two-phase interface through the improvement and innovation of molding technology. Traditional diamond / metal composite materials improve the interface performance and thermal conductivity of composite materials by surface modification of diamond particles, but the surface modification process is complicated, costly, and inefficient, and the modified layer is poorly bonded to the diamond, and the surface modification layer is uneven. At the same time, molding processes such as hot pressing sintering and spark plasma sintering have long process flows, low efficiency, instability, and low yield, making it difficult to prepare composite materials with complex structures. Therefore, it is urgent to develop a diamond / metal composite material with low cost and high performance and its preparation process, which can meet the requirements of low cost and short process preparation while achieving high thermal conductivity, low expansion and high strength. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention provides a three-dimensional continuous diamond / metal composite material and its preparation method and application. The method solves the difficult problem of preparing a porous diamond material blank and an interface protective layer by constructing a three-dimensional continuous silicon carbide combined with a diamond network and a metal network. The prepared composite material not only has an adjustable diamond volume fraction, thermal conductivity and thermal expansion coefficient, but can also be quickly prepared at low cost and in a short process, especially in the fields of heat dissipation materials, wear-resistant materials, functional structure integrated materials and bulletproof materials, showing a wide range of application prospects.
[0006] In a first aspect, the present invention provides a three-dimensional continuous diamond / metal composite material, wherein the three-dimensional continuous diamond / metal composite material is constructed by a three-dimensional continuous diamond network and a metal network in a mutually penetrating manner, wherein the three-dimensional continuous diamond network is formed by diamond particles having a silicon carbide protective layer formed on the surface connected by a diamond-silicon carbide phase boundary;
[0007] Wherein, the metal in the metal network is copper, aluminum, magnesium, copper alloy, aluminum alloy or magnesium alloy.
[0008] Preferably, the volume fraction of the three-dimensional continuous diamond network is 40%-80%, the porosity of the three-dimensional continuous diamond network is 20%-60%, the volume fraction of the diamond particles is 30%-75%, and the volume fraction of the silicon carbide protective layer is 5%-30%.
[0009] Preferably, the volume fraction of the three-dimensional continuous diamond network is 45%-72%, the porosity of the three-dimensional continuous diamond network is 28%-55%, the volume fraction of the diamond particles is 34%-65%, and the volume fraction of the silicon carbide protective layer is 7%-29%.
[0010] Preferably, the volume fraction of the three-dimensional continuous diamond network is 72%, the porosity of the three-dimensional continuous diamond network is 28%, the volume fraction of the diamond particles is 65%, and the volume fraction of the silicon carbide protective layer is 7%.
[0011] Preferably, the volume fraction of the three-dimensional continuous diamond network is 64%, the porosity of the three-dimensional continuous diamond network is 36%, the volume fraction of the diamond particles is 51%, and the volume fraction of the silicon carbide protective layer is 13%.
[0012] Preferably, the volume fraction of the three-dimensional continuous diamond network is 65%, the porosity of the three-dimensional continuous diamond network is 35%, the volume fraction of the diamond particles is 36%, and the volume fraction of the silicon carbide protective layer is 29%.
[0013] Preferably, the volume fraction of the three-dimensional continuous diamond network is 45%, the porosity of the three-dimensional continuous diamond network is 55%, the volume fraction of the diamond particles is 34%, and the volume fraction of the silicon carbide protective layer is 11%.
[0014] Preferably, a silicon carbide protective layer is formed on the surface of the diamond particles in the three-dimensional continuous diamond network, the thickness of the silicon carbide protective layer is 100 nm -1.0 μm, and the silicon carbide protective layer covers more than 90% of the surface area of the diamond particles.
[0015] More preferably, the thickness of the silicon carbide protective layer is 200 nm-0.8 μm.
[0016] Preferably, the pore size of the three-dimensional continuous diamond network is 50 nm-300 μm, and the diamond particle size is 50 μm-700 μm.
[0017] More preferably, the pore size of the diamond network is 50 nm-200 μm, and the diamond particle size is 100 μm-500 μm.
[0018] Preferably, the magnesium alloy is selected from magnesium-aluminum alloy, magnesium-manganese alloy, magnesium-lithium alloy, magnesium rare earth alloy, magnesium-silver alloy or magnesium-thorium alloy; the copper alloy is selected from brass, nickel silver or bronze; the aluminum alloy is selected from aluminum-silicon alloy, aluminum-magnesium-silicon alloy, aluminum-copper alloy, aluminum-magnesium alloy, aluminum-manganese alloy, aluminum-zinc alloy or aluminum-lithium alloy.
[0019] In a second aspect, the present invention provides a method for preparing the above three-dimensional continuous diamond / metal composite material, which comprises the following steps:
[0020] Step 1, preparation of slurry: diamond particles, silicon-based powder, binder, curing agent and solvent are mixed evenly to obtain slurry;
[0021] Step 2, granulation process: removing the solvent in the slurry, crushing and screening to obtain granular materials;
[0022] Step 3, forming process: pressing the granular material obtained in step 2 into a preform;
[0023] Step 4, pyrolysis process: pyrolyzing the preform obtained in step 3 to obtain a pyrolyzed preform;
[0024] Step 5, sintering process: sintering the pyrolysis preform obtained in step 4 at high temperature to obtain a three-dimensional continuous diamond network;
[0025] Step 6, composite process: pouring or infiltrating molten metal into the three-dimensional continuous diamond network prepared in step 5 to prepare a three-dimensional continuous diamond / metal composite material.
[0026] Preferably, in step 1, the ratio of diamond particles, silicon-based powder, binder, curing agent and solvent is 50 g-200 g of silicon-based powder, 50 g-200 g of binder, 10 g-100 g of curing agent and 500 mL-1000 mL of solvent for every 500 g of diamond particles.
[0027] Preferably, the silicon-based powder is one or both of metallic silicon powder and silicon dioxide powder.
[0028] Preferably, the binder is one or more of phenolic resin, epoxy resin, polyvinyl alcohol, polyvinyl butyral, furan resin, polyurethane, polycarbosilane, polyborazane, polyborosiloxane, polyborosilazane and polyzirconium borosilazane.
[0029] Preferably, the curing agent is a substance that can react with the binder and transform the binder from a liquid or semi-fluid state to a solid state.
[0030] Preferably, the curing agent is one of an amine curing agent, an anhydride curing agent, a phenolic curing agent, an imidazole curing agent, an acidic curing agent and a thiol curing agent.
[0031] The amine curing agent is selected from ethylenediamine, triethylenetetramine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, aliphatic diamines, aliphatic polyamines, aromatic polyamines, dicyandiamide, melamine, trimethylmelamine, and hexamethylenetetramine.
[0032] The acid anhydride curing agent is selected from, for example, phthalic anhydride, tetrahydrophthalic anhydride, phthalic anhydride, maleic anhydride, and trimellitic anhydride.
[0033] The phenolic curing agent is selected from terephthalaldehyde, phenol, hydroquinone, cresol, bisphenol A, bisphenol F, nonylphenol, resorcinol, formaldehyde, and glutaraldehyde.
[0034] The imidazole curing agent is selected from imidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-methylimidazole, 2-phenylimidazole, 4,5-dihydroxyimidazole, 2-isopropylimidazole, 2-aminoimidazole, N-ethylimidazole, and imidazole salts.
[0035] The acidic curing agent is selected from p-toluenesulfonic acid, citric acid, sulfuric acid, hydrochloric acid, phosphoric acid, oxalic acid, adipic acid, benzenesulfonic acid, petroleum sulfonic acid, acetic acid, formic acid, glycolic acid, lactic acid, hydroxysuccinic acid, propionic acid, fatty acid, boric acid, succinic acid, p-azidobenzoic acid.
[0036] The thiol curing agent is selected from 1,2,3-propanetrithiol, 1,2-ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 2-mercaptoethanol, 2-mercaptopropionic acid, mercaptopropanol, thioglycolic acid, dimercaptodiphenylethane (DMDE), mercaptoacetamide and polythioacrylate.
[0037] Preferably, the solvent is one or more of ethanol, acetone, ethylene glycol, toluene, xylene and water.
[0038] Preferably, in step 2, the method for removing the solvent in the slurry is selected from natural drying, freeze drying, spray drying, fluidized bed drying, belt drying, hollow paddle drying, disc drying, boiling drying, air flow drying, vacuum drying or hot air circulation drying.
[0039] Preferably, in step 2, the pulverizing method is mechanical pulverizing, for example, pulverizing using a crusher, wherein the crusher is selected from a jaw crusher, a cone crusher or an impact crusher.
[0040] Preferably, in step 2, the powder is crushed to obtain a powder with a particle size less than 0.5 mm.
[0041] Preferably, in step 2, granular material with a size of less than 150 mesh is obtained after screening.
[0042] Preferably, in step 2, granular material with a size of less than 120 mesh is obtained after screening.
[0043] Preferably, in step 3, the pressing pressure used for pressing into the preform is 50 MPa-100 MPa, the holding time is 10 min-60 min, and the temperature is 20°C-240°C.
[0044] Preferably, in step 4, the pyrolysis temperature is 600°C-1000°C, and the pyrolysis is carried out for 30 min-60 min.
[0045] Preferably, in step 4, an inert gas is used for protection during pyrolysis. More preferably, the inert gas is selected from helium, neon, and argon.
[0046] Preferably, in step 5, the high temperature sintering is performed in a protective atmosphere or in a vacuum condition, and the protective atmosphere is selected from one or both of argon protection and nitrogen protection.
[0047] Preferably, in step 5, the high temperature sintering temperature is 1450° C.-1750° C., and the sintering time is 5 min-60 min.
[0048] Preferably, in step 6, the metal of the molten metal is selected from copper, aluminum, magnesium, copper alloy, aluminum alloy or magnesium alloy; wherein the magnesium alloy is selected from magnesium-aluminum alloy, magnesium-manganese alloy, magnesium-lithium alloy, magnesium rare earth alloy, magnesium-silver alloy and magnesium-thorium alloy; the copper alloy is selected from brass, nickel silver and bronze; the aluminum alloy is selected from aluminum-silicon alloy, aluminum-magnesium-silicon alloy, aluminum-copper alloy, aluminum-magnesium alloy, aluminum-manganese alloy, aluminum-zinc alloy and aluminum-lithium alloy.
[0049] Preferably, in step 6, the pouring method is to preheat the three-dimensional continuous diamond network at a temperature of 600°C-1000°C under inert gas protection; at the same time, preheat the mold to 200°C-400°C; then place the preheated three-dimensional continuous diamond network into the mold, and pour the molten metal into the mold at a pouring temperature of 500°C-1450°C; pressurize and fill the mold, the applied pressure is 80 MPa-200 MPa, the pressurization time is greater than 5 s, and the pressure holding time is greater than 5 s.
[0050] The infiltration is a pressureless infiltration, in which the three-dimensional continuous diamond network is placed in a mold, and metal is placed on the upper part of the three-dimensional continuous diamond network. N2 protection is used, and the infiltration temperature is 600℃-1400℃. The temperature is kept for 0.1 h – 2 h. The metal melts into molten metal, and the molten metal infiltrates into the three-dimensional continuous diamond network.
[0051] The infiltration is pressure infiltration, where a three-dimensional continuous diamond network is placed in a mold, and metal is placed on top of it. The mold is vacuumed, the infiltration temperature is 500℃-1400℃, and the temperature is kept for 0.1 h-2 h. The mold is inflated and pressurized to a pressure of 0.1 MPa-12 MPa, and the molten metal is infiltrated into the three-dimensional continuous diamond network.
[0052] In a third aspect, the present invention provides an application of a three-dimensional continuous diamond / metal composite material, wherein the three-dimensional continuous diamond / metal composite material is used for heat dissipation materials, wear-resistant materials, functional structure integrated materials, and bulletproof materials.
[0053] Among them, functional structural integrated materials are a type of composite materials that have both load-bearing capacity (structural function) and can achieve specific physical, chemical or biological functions. It breaks through the traditional material design of separation between structure and function, and through the coordinated design of materials and structures, it can simultaneously meet the functional and structural requirements. In addition to having good mechanical properties, the composite material of the present invention also has good thermal conductivity and can be used as a functional structural integrated material, heat dissipation material, wear-resistant material, and bulletproof material.
[0054] In summary, the present invention has the following beneficial effects:
[0055] 1. The three-dimensional continuous diamond / metal composite material of the present invention is constructed by a three-dimensional continuous diamond network and a metal network through mutual penetration. Among them, the diamond network is formed by diamond particles with a silicon carbide protective layer formed on the surface connected by a diamond-silicon carbide phase boundary. By adopting the preparation method of the present invention, a highly thermally conductive diamond / metal composite material with highly adjustable diamond volume fraction, thermal conductivity, and thermal expansion coefficient can be obtained. Among them, the thermal conductivity range is 423 W / m·K-572W / m·K, and the linear expansion coefficient (0-100 o C) 5.9 × 10 -6 / K -7.0×10 -6 / K, the flexural strength range is 323 MPa -378 MPa.
[0056] 2. The three-dimensional continuous diamond network prepared by the present invention is connected by diamond-silicon carbide phase boundaries to ensure the high strength of the three-dimensional continuous diamond network. At the same time, the silicon carbide layer formed on the surface of the diamond particles plays a surface modification role.
[0057] 3. The three-dimensional continuous diamond / metal composite material prepared by the present invention has adjustable diamond volume fraction and porosity, which is conducive to being suitable for different application environments.
[0058] 4. The three-dimensional continuous diamond / metal composite material prepared by the present invention has the characteristics of high mechanical properties, low expansion coefficient, high thermal conductivity, etc., and is isotropic, with a short preparation process and low cost, which can meet market demand.
[0059] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is a scanning electron microscope result image of the three-dimensional continuous diamond network obtained through the sintering process in Example 1 of the present invention, which shows the microscopic morphology of the diamond network with a silicon carbide protective layer obtained after sintering at 1650°C.
[0061] Figure 2 This is a scanning electron microscope result image of the three-dimensional continuous diamond network obtained through the sintering process in Example 1 of the present invention, which shows the microscopic morphology of the surface silicon carbide protective layer of the diamond network obtained after sintering at 1650°C. DETAILED DESCRIPTION
[0062] The present invention is further described in detail below with reference to the embodiments.
[0063] Example 1
[0064] In this embodiment, the preparation process of the three-dimensional continuous diamond / metal composite material is as follows:
[0065] Step 1, preparation of slurry: mix diamond particles (particle size 100 μm), metal silicon powder (average particle size 3.5 μm), phenolic resin (binder), p-toluenesulfonic acid (curing agent), and ethanol in a ratio of 500 g: 80 g: 100 g: 10 g: 1000 mL, and prepare a slurry by fully ball milling.
[0066] Step 2, granulation process
[0067] Step 2-1 Drying: Dry the slurry obtained in step 1 to remove the solvent and obtain a dry material. The drying process adopts a vacuum drying process at a temperature of 80° C. and is kept warm for 4 hours.
[0068] Step 2-2 Crushing: The material obtained in step 2-1 is crushed into powder with a particle size of less than 0.5 mm using an impact crusher.
[0069] Step 2-3 Screening: Screen the material obtained in step 2-2 to obtain material with a mesh size smaller than 120.
[0070] Step 3, molding process
[0071] The material with a mesh size less than 120 mesh screened out in step 2-3 was pressed into a preform using a mold at a temperature of 25°C and a pressure of 100 MPa for 10 min.
[0072] Step 4, pyrolysis process
[0073] The preform was pyrolyzed under inert gas protection to obtain a pyrolysis preform. The pyrolysis temperature reached 850 °C at a heating rate of 1 °C / min and was kept at this temperature for 45 min.
[0074] Step 5, sintering process
[0075] The pyrolysis preform obtained in step 4 is sintered at high temperature under vacuum conditions at a temperature of 1650° C. for 60 min to obtain a three-dimensional continuous diamond network.
[0076] Step 6: Compounding process
[0077] The three-dimensional continuous diamond network was placed in a box furnace for preheating at 700°C under inert gas protection; at the same time, the mold was preheated to 300°C; then the preheated three-dimensional continuous diamond network was placed in the mold, and the aluminum alloy ZL101 melt was poured into the mold at a pouring temperature of 700°C; the mold was pressurized and filled with a pressure of 100 MPa, a pressurizing time of 30 s, and a pressure holding time of more than 30 s; after cooling, a three-dimensional continuous diamond / metal composite material was obtained.
[0078] like Figure 1 As shown, the microscopic morphology of the three-dimensional continuous diamond network obtained after the sintering process in step 5 of Example 1 was observed by scanning electron microscopy, and it can be seen that the diamond network is in the form of a porous network with uniform pore distribution. The pore size of the diamond network is about 50 nm-200 μm.
[0079] like Figure 2 As shown, the microscopic morphology of the three-dimensional continuous diamond network obtained after the sintering process in step 5 of Example 1 is observed by scanning electron microscopy, and it can be seen that a silicon carbide protective layer is formed on the surface of the diamond particles. The thickness of the silicon carbide protective layer is about 0.2 μm - 0.8 μm, and the silicon carbide protective layer basically covers the surface area of the diamond particles, covering more than 90% of the surface area of the diamond particles.
[0080] It can be seen that the diamond particles with silicon carbide protective layers formed on the surface are connected through the diamond-silicon carbide phase boundary to form a three-dimensional continuous diamond network. The three-dimensional continuous diamond network is then subjected to the composite process of step 6, and the three-dimensional continuous diamond network and the metal alloy network penetrate each other to form a three-dimensional continuous diamond / metal composite material.
[0081] In this embodiment, the technical indicators of the three-dimensional continuous diamond / metal composite material are as follows:
[0082] The thermal conductivity is 437W / m·K, and the linear expansion coefficient (0-100℃) is 6.1×10 -6 / K, and the bending strength is 357 MPa. The volume fraction of the three-dimensional continuous diamond network is 72%, the porosity of the three-dimensional continuous diamond network is 28%, the volume fraction of the diamond particles is 65%, and the volume fraction of the silicon carbide protective layer is 7%. The volume fraction of the three-dimensional continuous diamond network is the percentage of the volume of the three-dimensional continuous diamond network to the volume of the three-dimensional continuous diamond / metal composite material, the porosity of the three-dimensional continuous diamond network is the volume percentage of the three-dimensional continuous diamond / metal composite material except the three-dimensional continuous diamond network, and the sum of the porosity of the three-dimensional continuous diamond network and the volume fraction of the three-dimensional continuous diamond network is 100%; the volume fraction of the diamond particles is the percentage of the volume of the diamond particles in the three-dimensional continuous diamond network to the volume of the three-dimensional continuous diamond / metal composite material; the volume fraction of the silicon carbide protective layer is the percentage of the volume of the silicon carbide protective layer on the surface of the diamond particles in the three-dimensional continuous diamond network to the volume of the three-dimensional continuous diamond / metal composite material.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that the phenolic resin in step 1 is replaced by a mixture of phenolic resin, epoxy resin and polyvinyl alcohol.
[0085] Step 1 is replaced by mixing diamond particles (particle size 200 μm), metal silicon powder (average particle size 10 μm), a mixture of phenolic resin, epoxy resin and polyvinyl alcohol (binder), p-toluenesulfonic acid (curing agent), and ethanol in a ratio of 500 g: 50 g: 50 g: 10 g: 1000 mL, and fully ball-milling the mixture to form a slurry.
[0086] In this embodiment, the technical indicators of the three-dimensional continuous diamond / metal composite material are as follows:
[0087] Thermal conductivity is 572 W / m·K, linear expansion coefficient (0-100 ℃) is 6.7×10 -6 / K, flexural strength 323 MPa.
[0088] The volume fraction of the three-dimensional continuous diamond network is 64%, the porosity of the three-dimensional continuous diamond network is 36%, the volume fraction of the diamond particles is 51%, and the volume fraction of the silicon carbide protective layer is 13%.
[0089] Example 3
[0090] The difference between this embodiment and embodiment 1 is that the conditions for pressing the preform in step 3 are replaced by a temperature of 180° C., a pressure of 50 MPa, and a pressure holding time of 20 min.
[0091] In this embodiment, the technical indicators of the three-dimensional continuous diamond / metal composite material are as follows:
[0092] Thermal conductivity is 456 W / m·K, linear expansion coefficient (0-100 o C) is 5.9×10 -6 / K, flexural strength is 378MPa.
[0093] The volume fraction of the three-dimensional continuous diamond network is 72%, the porosity of the three-dimensional continuous diamond network is 28%, the volume fraction of the diamond particles is 65%, and the volume fraction of the silicon carbide protective layer is 7%.
[0094] Example 4
[0095] The difference between this embodiment and embodiment 1 is that step 6 is replaced by placing the three-dimensional continuous diamond network into a mold, placing aluminum alloy on the upper part of the three-dimensional continuous diamond network, vacuum infiltration, the infiltration temperature is 100°C, the temperature is kept for 0.1h, and the pressure is inflated and pressurized to 12 MPa; after cooling, a three-dimensional continuous diamond / metal composite material is obtained.
[0096] In this embodiment, the technical indicators of the three-dimensional continuous diamond / metal composite material are as follows:
[0097] Thermal conductivity is 479 W / m·K, linear expansion coefficient (0-100 o C) is 6.0×10 -6 / K, flexural strength is 365MPa.
[0098] The volume fraction of the three-dimensional continuous diamond network is 72%, the porosity of the three-dimensional continuous diamond network is 28%, the volume fraction of the diamond particles is 65%, and the volume fraction of the silicon carbide protective layer is 7%.
[0099] Example 5
[0100] The difference between this embodiment and embodiment 4 is that the phenolic resin in step 1 is replaced by a mixture of phenolic resin and epoxy resin.
[0101] Step 6 is replaced by placing the three-dimensional continuous diamond into a mold, placing magnesium alloy AZ31 on the top of the three-dimensional continuous diamond, vacuum infiltrating, the infiltration temperature is 500°C, keeping warm for 2 hours, inflating and pressurizing, the pressure is 0.1 MPa; after cooling, a three-dimensional continuous diamond / metal composite material is obtained.
[0102] In this embodiment, the technical indicators of the three-dimensional continuous diamond / metal composite material are as follows:
[0103] Thermal conductivity is 423 W / m·K, linear expansion coefficient (0-100 o C) is 7.0×10 -6 / K bending strength is 363 MPa.
[0104] The volume fraction of the three-dimensional continuous diamond network is 72%, the porosity of the three-dimensional continuous diamond network is 28%, the volume fraction of the diamond particles is 65%, and the volume fraction of the silicon carbide protective layer is 7%.
[0105] Example 6
[0106] The difference between this embodiment and embodiment 1 is that step 1 is replaced by mixing diamond particles (particle size 100 μm), silicon dioxide powder (average particle size 100 nm), epoxy resin (binder), terephthalic acid aldehyde (curing agent), and ethanol in a ratio of 500 g: 50 g: 50 g: 25 g: 500 mL, and fully ball-milling the mixture to form a slurry.
[0107] The volume fraction of the three-dimensional continuous diamond network is 45%, the porosity of the three-dimensional continuous diamond network is 55%, the volume fraction of the diamond particles is 34%, and the volume fraction of the silicon carbide protective layer is 11%.
[0108] Example 7
[0109] The difference between this embodiment and embodiment 1 is that step 1 is replaced by mixing diamond particles (particle size 500 μm), metal silicon powder (average particle size 10 μm), polyvinyl butyral (binder), glutaraldehyde (curing agent), and ethanol in a ratio of 500 g: 200 g: 200 g: 100 g: 1000 mL, and fully ball-milling the mixture to form a slurry.
[0110] The volume fraction of the three-dimensional continuous diamond network is 65%, the porosity of the three-dimensional continuous diamond network is 35%, the volume fraction of the diamond particles is 36%, and the volume fraction of the silicon carbide protective layer is 29%.
[0111] Example 8
[0112] The difference between this embodiment and embodiment 1 is that step 1 is replaced by mixing diamond particles (particle size 200 μm), silicon dioxide powder (average particle size 10 μm), furan resin (binder), phthalic anhydride (curing agent), and ethanol in a ratio of 500 g: 100 g: 100 g: 50 g: 1000 mL, and fully ball-milling the mixture to form a slurry.
[0113] In step 4, the pyrolysis temperature is 600°C, and the pyrolysis is maintained for 60 min.
[0114] In step 5, the high temperature sintering temperature is 1450°C and the sintering time is 60 min.
[0115] Step 6 uses pressureless infiltration of composite metal and diamond, places the three-dimensional continuous diamond network into a mold, places metal on the upper part of the three-dimensional continuous diamond network, uses N2 protection, the infiltration temperature is 1400°C, and is kept warm for 0.1 h. The metal melts into molten metal, and the molten metal infiltrates into the three-dimensional continuous diamond network.
[0116] Example 9
[0117] The difference between this embodiment and embodiment 1 is that the phenolic resin in step 1 is replaced by polyvinyl alcohol; and p-toluenesulfonic acid is replaced by phenol.
[0118] The conditions for pressing the preform in step 3 are replaced by a temperature of 200 °C, a pressure of 100 MPa, and a pressure holding time of 20 min;
[0119] In step 4, the pyrolysis temperature is 1000°C, and the pyrolysis is carried out for 30 min.
[0120] In step 5, the high temperature sintering temperature is 1750°C and the sintering time is 5 min.
[0121] Step 6 uses pressureless infiltration of composite metal and diamond, places the three-dimensional continuous diamond network into a mold, places metal on the upper part of the three-dimensional continuous diamond network, uses N2 protection, the infiltration temperature is 600°C, and is kept warm for 2 hours. The metal melts into molten metal, and the molten metal infiltrates into the three-dimensional continuous diamond network.
[0122] Example 10
[0123] The difference between this embodiment and embodiment 1 is that the phenolic resin in step 1 is replaced by polyurethane; and p-toluenesulfonic acid is replaced by ethylenediamine.
[0124] The conditions for pressing the preform in step 3 are replaced by a temperature of 220° C., a pressure of 50 MPa, and a pressure holding time of 30 min.
[0125] Embodiment 11
[0126] The difference between this embodiment and embodiment 1 is that the phenolic resin in step 1 is replaced by polycarbosilane; and p-toluenesulfonic acid is replaced by imidazole.
[0127] Step 6 is replaced by placing the three-dimensional continuous diamond into a mold, placing aluminum alloy on the top of the three-dimensional continuous diamond, vacuum infiltrating, the infiltration temperature is 1000°C, keeping warm for 1 hour, inflating and pressurizing, the pressure is 8 MPa, and the aluminum alloy melt infiltrates into the three-dimensional continuous diamond network.
[0128] Example 12
[0129] The difference between this embodiment and embodiment 1 is that the phenolic resin in step 1 is replaced by polyborazine; and p-toluenesulfonic acid is replaced by 1,2,3-propanetrithiol.
[0130] Step 6 is replaced by placing the three-dimensional continuous diamond into a mold, placing aluminum alloy on the top of the three-dimensional continuous diamond, vacuum infiltrating, the infiltration temperature is 1200°C, keeping warm for 1 hour, inflating and pressurizing, the pressure is 8 MPa, and the aluminum alloy melt infiltrates into the three-dimensional continuous diamond network.
[0131] Embodiment 13
[0132] The difference between this embodiment and embodiment 4 is that the phenolic resin in step 1 is replaced by polyborazine; and p-toluenesulfonic acid is replaced by succinic acid.
[0133] The metal used is aluminum-magnesium-silicon alloy.
[0134] Embodiment 14
[0135] The difference between this embodiment and embodiment 4 is that the phenolic resin in step 1 is replaced by polyborosiloxane; and p-toluenesulfonic acid is replaced by thioglycolic acid.
[0136] The metal used is a magnesium-thorium alloy.
[0137] Embodiment 15
[0138] The difference between this embodiment and embodiment 4 is that the phenolic resin in step 1 is replaced by polyborosilazane; and p-toluenesulfonic acid is replaced by 2-methylimidazole.
[0139] The metal is aluminum-zinc alloy.
[0140] By observing the three-dimensional continuous diamond network blocks obtained by the sintering process in step 5 of the above embodiment through a scanning electron microscope, it can be observed that Figure 1-2 Similar microscopic morphologies of silicon carbide combined with diamonds indicate that a three-dimensional continuous diamond network can be formed by the method of the present invention. The combination of metal and this three-dimensional continuous diamond network will inevitably form a structure in which the three-dimensional continuous diamond network and the metal alloy network penetrate each other. At the same time, it can be found through observation that the diamond particles form a three-dimensional continuous diamond network due to the silicon carbide protective layer formed on the surface, connected by the diamond-silicon carbide phase boundary.
[0141] In the present invention, silicon-based powder, adhesive and curing agent are arranged on the outer surface of diamond particles, and the silicon-based powder, adhesive and curing agent mixture can form a silicon carbide protective layer on the surface of diamond particles through a molding process, a pyrolysis process and a sintering process, and the diamond particles are connected through the diamond-silicon carbide phase boundary to form a three-dimensional continuous diamond network. The adhesive and curing agent used in the present invention mainly serve the purpose of bonding diamonds and providing a carbon source in silicon carbide. Carbon-containing adhesives and matching curing agents with similar functions known in the art can be selected for use.
[0142] The results of Examples 1-15 show that the three-dimensional continuous diamond / metal composite material of the present invention has a three-dimensional continuous diamond network formed by connecting diamond particles through the diamond-silicon carbide phase boundary, which makes the preparation process of the three-dimensional continuous diamond preform short and low-cost, and can prepare a three-dimensional continuous diamond preform with a complex shape. At the same time, the three-dimensional continuous diamond / metal composite material has excellent thermophysical properties and mechanical properties, and is isotropic, and has great application value in the preparation of the third-generation semiconductor heat dissipation material "diamond / metal composite material".
[0143] Comparative Example 1
[0144] Nano-SiC coating was prepared on diamond surface by sol-gel method combined with in-situ reduction. Diamond particles (particle size 100 μm) were coated with SiO2 sol with pH value of 7.5 and molar concentration of 0.2 mol / L. Diamond coated with SiO2 sol was sintered in a vacuum furnace with a heating rate of 5 ℃ / min and kept at 1450 ℃ for 2 h before being cooled with the furnace. Then, 60% volume ratio diamond with nano-SiC coating was mechanically mixed and hot pressed with 50 μm 6061 aluminum alloy powder at a temperature of 620 ℃ and a pressure of 50 MPa to obtain 60% diamond aluminum composite material.
[0145] In this comparative example, the technical indicators of the 60% diamond / aluminum composite material are as follows:
[0146] Thermal conductivity is 373 W / m·K, linear expansion coefficient (0-100 o C) is 7.5×10 -6 / K, flexural strength is 180MPa.
[0147] Comparative Example 2
[0148] Nano-TiC coating was prepared on the surface of diamond by sol-gel method. Diamond particles (size 200 μm) were coated with TiO2 sol with pH value of 7.5 and molar concentration of 0.2 mol / L, and sintered at 1450 ℃ for 2 hours to form a uniform TiC coating on the surface of diamond. Then, 60% diamond with nano-TiC coating was mechanically mixed and hot-pressed with 50 μm 6061 aluminum alloy powder at 620 ℃ and 50 MPa to obtain 60% diamond aluminum composite material.
[0149] In this comparative example, the technical indicators of the 60% diamond / metal composite material are as follows:
[0150] Thermal conductivity is 300 W / m·K, linear expansion coefficient (0-100 o C) is 7.0×10 -6 / K, flexural strength is 200MPa.
[0151] Comparative Example 3
[0152] Nano-SiC coating was prepared on the surface of diamond by combining sol-gel method with in-situ reduction. Diamond particles (particle size 100 μm) were coated with SiO2 sol with pH value of 7.5 and molar concentration of 0.15 mol / L. Diamond coated with SiO2 sol was sintered in a vacuum furnace with a heating rate of 10 ℃ / min and kept at 1500 ℃ for 3 h before cooling with the furnace. After that, 60% diamond with nano-SiC coating was mechanically mixed and hot-pressed with 50 μm 6061 aluminum alloy powder at a temperature of 620 ℃ and a pressure of 80 MPa to obtain a 60% diamond aluminum composite material.
[0153] In this comparative example, the technical indicators of the 60% diamond / metal composite material are as follows:
[0154] Thermal conductivity is 415 W / m·K, linear expansion coefficient (0-100 o C) is 7.1×10 -6 / K, flexural strength is 230MPa.
[0155] Comparative Example 4
[0156] Nano-SiC coating was prepared on diamond surface by sol-gel method combined with in-situ reduction technology. Diamond particles (particle size 100 μm) were coated with SiO2 sol with pH value of 7.5 and molar concentration of 0.2 mol / L. Diamond coated with SiO2 sol was sintered in a vacuum furnace with a heating rate of 5 ℃ / min and kept at 1450 ℃ for 2 h before being cooled with the furnace. After that, 60% diamond with nano-SiC coating was mechanically mixed and hot-pressed with 60 μm AZ31 magnesium alloy powder at a temperature of 570℃ and a pressure of 100 MPa to obtain a 60% diamond metal composite material.
[0157] In this comparative example, the technical indicators of the 60% diamond / metal composite material are as follows:
[0158] Thermal conductivity is 269 W / m·K, linear expansion coefficient (0-100 o C) is 7.4×10 -6 / K, flexural strength is 170MPa.
[0159] By comparison with the comparative example, it can be seen that since the comparative example adopts a method different from the preparation method of the present invention, a three-dimensional continuous diamond network cannot be obtained. From the perspective of technical indicators, it can be seen that although both are composite materials of diamond and metal, since the comparative example does not contain a three-dimensional continuous diamond network, its ability to resist bending stress is weaker than that of the composite material of the present invention. At the same time, since it is constructed by the mutual penetration of the three-dimensional continuous diamond network and the metal network, its thermal conductivity is significantly improved. Therefore, although the comparative example uses the same type of metal and the same size of diamond as Examples 1-5, since it does not form a three-dimensional continuous diamond network, its thermal conductivity is low.
[0160] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A three-dimensional continuous diamond / metal composite material, characterized in that: The three-dimensional continuous diamond / metal composite material is constructed by a three-dimensional continuous diamond network and a metal network in a mutually penetrating manner, and the three-dimensional continuous diamond network is formed by diamond particles with a silicon carbide protective layer formed on the surface connected through a diamond-silicon carbide phase boundary; Wherein, the metal in the metal network is copper, aluminum, magnesium, copper alloy, aluminum alloy or magnesium alloy.
2. The three-dimensional continuous diamond / metal composite material according to claim 1, characterized in that: The volume fraction of the three-dimensional continuous diamond network is 40%-80%, the porosity of the three-dimensional continuous diamond network is 20%-60%, the volume fraction of diamond particles is 30%-75%, and the volume fraction of the silicon carbide protective layer is 5%-30%.
3. A method for preparing a three-dimensional continuous diamond / metal composite material, characterized in that: The preparation method is used to prepare the three-dimensional continuous diamond / metal composite material according to any one of claims 1 to 2, and the preparation method comprises the following steps: Step 1, preparation of slurry: diamond particles, silicon-based powder, binder, curing agent and solvent are mixed evenly to obtain slurry; Step 2, granulation process: removing the solvent in the slurry, crushing and screening to obtain granular materials; Step 3, forming process: pressing the granular material obtained in step 2 into a preform; Step 4, pyrolysis process: pyrolyzing the preform obtained in step 3 to obtain a pyrolyzed preform; Step 5, sintering process: sintering the pyrolysis preform obtained in step 4 at high temperature to obtain a three-dimensional continuous diamond network; Step 6, composite process: pouring or infiltrating molten metal into the three-dimensional continuous diamond network prepared in step 5 to prepare a three-dimensional continuous diamond / metal composite material.
4. The preparation method according to claim 3, characterized in that: In step 1, the ratio of diamond particles, silicon-based powder, binder, curing agent, and solvent is 50 g to 200 g of silicon-based powder, 50 g to 200 g of binder, 10 g to 100 g of curing agent, and 500 mL to 1000 mL of solvent for every 500 g of diamond particles.
5. The preparation method according to claim 3, wherein the silicon-based powder is one or both of metallic silicon powder and silicon dioxide powder; The binder is selected from one or more of phenolic resin, epoxy resin, polyvinyl alcohol, polyvinyl butyral, furan resin, polyurethane, polycarbosilane, polyborazane, polyborosiloxane, polyborosilazane and polyzirconium borosilazane; the curing agent is selected from amine curing agent, acid anhydride curing agent, phenolic curing agent, imidazole curing agent, acidic curing agent or thiol curing agent.
6. The preparation method according to claim 3, characterized in that: In step 2, the method for removing the solvent in the slurry is selected from natural drying, freeze drying, spray drying, fluidized bed drying, belt drying, hollow paddle drying, disc drying, boiling drying, air flow drying, vacuum drying or hot air circulation drying; the pulverizing method is mechanical pulverization, pulverizing to obtain a powder with a particle size of less than 0.5 mm; and sieving to obtain a granular material below 150 mesh.
7. The preparation method according to claim 3, characterized in that: In step 3, the pressing pressure used for pressing into the preform is 50 MPa-100 MPa, the holding time is 10 min-60 min, and the temperature is 20 ℃-240 ℃.
8. The preparation method according to claim 3, characterized in that: In step 6, the metal of the molten metal is selected from copper, aluminum, magnesium, copper alloy, aluminum alloy or magnesium alloy; the magnesium alloy is selected from magnesium-aluminum alloy, magnesium-manganese alloy, magnesium-lithium alloy, magnesium rare earth alloy, magnesium-silver alloy or magnesium-thorium alloy; the copper alloy is selected from brass, nickel silver or bronze; the aluminum alloy is selected from aluminum-silicon alloy, aluminum-magnesium-silicon alloy, aluminum-copper alloy, aluminum-magnesium alloy, aluminum-manganese alloy, aluminum-zinc alloy or aluminum-lithium alloy.
9. The preparation method according to claim 3, characterized in that: In step 6, the pouring method is to preheat the three-dimensional continuous diamond network at a temperature of 600°C-1000°C under inert gas protection; at the same time, preheat the mold to 200°C-400°C; then place the preheated three-dimensional continuous diamond network into the mold, and pour the molten metal into the mold at a pouring temperature of 500°C-1450°C; pressurize and fill the mold, the applied pressure is 80 MPa-200 MPa, the pressurization time is greater than 5 s, and the pressure holding time is greater than 5 s; The infiltration is pressureless infiltration, where the three-dimensional continuous diamond network is placed in a mold, and metal is placed on the upper part of the three-dimensional continuous diamond network. N2 protection is used, and the infiltration temperature is 600℃-1400℃. The temperature is kept for 0.1 h – 2 h. The metal is melted into molten metal, and the molten metal is infiltrated into the three-dimensional continuous diamond network; or The infiltration is pressure infiltration, where a three-dimensional continuous diamond network is placed in a mold, and metal is placed on top of it. The mold is vacuumed, the infiltration temperature is 500℃-1400℃, and the temperature is kept for 0.1 h-2 h. The mold is inflated and pressurized to a pressure of 0.1 MPa-12 MPa, and the molten metal is infiltrated into the three-dimensional continuous diamond network.
10. An application of a three-dimensional continuous diamond / metal composite material, characterized in that: The three-dimensional continuous diamond / metal composite material described in any one of claims 1-2 is used for heat dissipation materials, wear-resistant materials, functional structure integrated materials, and bulletproof materials.
Citation Information
Patent Citations
Method for preparing carborundum and diamond particle reinforced aluminum-base composite material
CN103540830A
Preparation method of diamond / metal-based composite material with high volume fraction
CN103981392A
Technological method of manufacturing diamond / aluminum composite material through pressure-free infiltration method
CN109777987A
High-thermal-conductivity pure porous silicon carbide material, preparation method and application thereof
CN110746192A
Low-cost preparation method of high-thermal-conductivity diamond reinforced metal matrix composite material
CN112981205A
Cited By
Diamond-metal composite material with six surfaces coated with metal as well as processing method and application of diamond-metal composite material
CN120243943A
Silicon carbide-diamond porous composite material as well as preparation method and application thereof
CN120590164A
